The Acceptance and Use of Online Technology in Thailand: The Influences of Perceived Trust and Personal Innovativeness on the UTAUT Model - Chayomchai, Ampol; Petmee, Peyawan; Khowjoy, Kritchai; Phatanasakoo, Ajchareeya; Suwannapusit, Ubonwan (International Journal of Psychosocial Rehabilitation, 2020)
The main objectives of this research were to study the relationship of all factors in the UTAUT model, to examine the effect of perceived trust on performance expectancy, effort expectancy, and behavioral intention, and to test the effect of personal innovativeness on the intention to use technology. The authors utilized online questionnaires to collect the data by convenience sampling method. Data of 510 respondents were used for statistical analysis. The author utilized PLS-SEM assessment for examining the research hypothesis. The results revealed that performance expectancy, effort expectancy, perceived trust, and personal innovativeness positively affected behavioral intention to use online technology. Another finding is the perceived trust had a positive and significant influence on both performance expectancy and effort expectancy. A further finding of this research was facilitating conditions significantly affected actual use behavior of online technology. The last finding of this research proved that the behavioral intention to use online technology had a strong positive effect on the actual use behavior. The researchers suggest the benefits of this study to the corporate executives or the marketing department who have to plan for the online technology business to Thai people. Following the significant effect of key factors on users’ behavior, the end result should improve the acceptance of online technology and lead to actual use behavior of Thai users in online technologies. gy8